Gendered syndemic of intimate partner violence, alcohol misuse, and HIV risk among peri-urban, heterosexual men in South Africa. (February 2022) - Hatcher, Abigail M.; Gibbs, Andrew; McBride, Ruari-Santiago; Rebombo, Dumisani; Khumalo, Mzwakhe; Christofides, Nicola J.
Abstract: Men whose sexual behaviors place them at risk of HIV often exhibit a "cluster" of behaviors, including alcohol misuse and violence against women. Called the "Substance Abuse, Violence and AIDS (SAVA) syndemic, " this intersecting set of issues is poorly understood among heterosexual men in sub-Saharan Africa. We aim to determine cross-sectional associations between men's use of alcohol, violence, and HIV risk behaviors using a gendered syndemics lens. We conducted a baseline survey with men in an informal, peri-urban settlement near Johannesburg (Jan–Aug 2016). Audio-assisted, self-completed questionnaires measured an index of risky sex (inconsistent condom use, multiple partnerships, transactional sex), recent violence against women (Multicountry Study instrument), alcohol misuse (Alcohol Use Disorders Tool), and gender attitudes (Gender Equitable Men's Scale). We used logistic regression to test for syndemic interaction on multiplicative and additive scales and structural equation modeling to test assumptions around serially causal epidemics. Of 2454 men, 91.8% reported one or more types of risky sex. A majority of participants reported one or more SAVA conditions (1783, 71.6%). After controlling for socio-demographics, higher scores on the risky sex index were independently predicted by men's recent violence use, problem drinking, and inequitable gender views. Those men reporting all three SAVA conditions had more than 12-fold greater odds of risky sex compared to counterparts reporting no syndemic conditions. Each two-way interaction of alcohol use, gender inequitable views, and IPV perpetration was associated with a relative increase in risky sex on either a multiplicative or additive scale. A structural equation model illustrated that gender norms predict violence, which in turn predict alcohol misuse, increasing both IPV perpetration and risky sex. These data are consistent with a syndemic model of HIV risk among heterosexual men. Targeting intersections between syndemic conditions may help prevent HIV among heterosexual men in peri-urban African settings. Highlights: Heterosexual men's risky sex overlaps with alcohol and violence against women. We used a "gendered syndemic" lens to explore substance use, violence, and HIV/AIDS. We found gender norms predict violence, which leads to alcohol and risky sex. Targeting syndemics among heterosexual men may ensure health in peri-urban settings. This is among the first papers to offer quantitative support for syndemic theory.